The Customers’ Determinant Factors of the Bank Selection - Krisnanto, Umbas (International Research Journal of Business Studies, 2011)
Some previous researchers are still arguing about the factors that determine the selection of a bank. These factors depend on the intensity of marketing activities undertaken by the bank, reputation of the bank, credit availability, friendly staffs, appropriate interest rates, and location. Jakarta was selected for the research location since Jakarta is the biggest city in Indonesia that represents the advancement of the banking industry. Different statistics tools are applied to find the accurate opinion why respondent choose a bank. Based on the results, the research concludes factors that determine in selecting a bank tend to be based on the secondary factors such as recommendation from friends, and advice from family members.